Comparative evaluation of ultrasonography and computed tomography findings in focal hepatic masses - Bali, Simran; Kaur, Amarjit; Kaur Mohi, Jaswinder; Kumar, Ashwani; Sachayta, Sachayta; Singh, Jasvir (International Journal of Medical Research and Review, 2017)
Introduction: Focal liver lesions are defined as solid or liquid-containing masses foreign to the normal anatomy of the liver that may be told apart from the latter organ using imaging techniques. They can have a number of etiologies including congenital, neoplastic and infectious and inflammatory conditions as well as trauma and miscellaneous entities. The data was analyzed to compare between ultrasonography (USG) and computed tomography (CT) findings in these cases. Aims and Objectives: To evaluate the role of ultrasound and computed tomography in diagnosis of focal hepatic masses and compare the ultrasound and CT findings of focal hepatic masses and correlate with histopathological and surgical findings. Material and Methods: USG and CT were performed on 40 focal hepatic mass patients. The diagnostic value of ultrasound was compared to those of CT. Final diagnosis was made after correlation with surgical findings, serological findings and histopathological examination. The data collected was analyzed statistically. Results: Final diagnosis of focal hepatic masses was simple cysts (n=5), polycystic liver (n=1), metastasis (n=22), hydatid cysts(n=5), hemangioma (n=6), hepatocellular (n=11), focal nodular hyperplasia (n=1), abscess (n=16), cholangiocarcinoma (n=1). The sensitivity, specificity positive and negative likelihood ratio were 84.38%, 67.74%, 2.62 and 0.23 respectively, for USG and 100%, 97.14%, 35 and 0 respectively, for CT. Conclusion: USG and CT are the modalities having comparable specificity and sensitivity, CT being slightly more accurate than USG in evaluation of focal hepatic lesions in atypical cases. USG is useful in follow-up cases.